Rhodium(I)-Catalyzed Cycloisomerization of 1,6-Enynes - Matsushima, Yuji; Phillips, Eric M.; Bergman, Robert G.; Ellman, Jonathan A. (Synlett, 2015)
A new and unexpected rhodium(I)-catalyzed cycloisomerization of 1,6-enynes is reported. Several different alkyne substitution patterns were evaluated under the reaction conditions, including a deuterated derivative that provides some insight into the reaction mechanism.
Keywords: rhodium; homogeneous catalysis; ring closure; isomerization; enones